The Impact of Gender Inequality on Trade in Ghana: An Empirical Study - Atuilik, Daniel Abayaakadina (2017)
A Thesis submitted to the Department of Economics of the College of Social Sciences and Humanities, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the award of Master of Science Degree in Economics.